Relationships between depression, anxiety, and residual problems following recovery from Guillain-Barré Syndrome : a New Zealand survey : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Bourke, Cecilia (Massey University, 2001)
The present study retrospectively examined the relationships between mental status and residual problems following recovery from Guillain-Barré Syndrome (GBS), and investigated whether depression and anxiety were common post GBS sequelae. Participants were drawn from past and present GBS patients who read about the postal survey in the newsletter of the New Zealand GBS Support Group. Of the 49 adults who responded, 44 individuals completed and returned the questionnaires sent to them via the Support Group Co-ordinator. The set of 4 questionnaires comprised (a) a brief questionnaire about GBS, (b) the McMaster Health Index Questionnaire (MHIQ), a generic quality of life instrument that measures physical, social, and emotional functioning, (c) the Beck Depression Inventory-II (BDI-II), and (d) the 6-Item Short Form of the State Scale of the State-Trait Anxiety Inventory (STAI-6). The MHIQ was completed twice, retrospectively from the point in time when GBS was most severe, and from the present point in time The results showed that half the sample were acutely ill over 6 years ago, yet the majority of the sample reported a number of residual problems with varying levels of severity. Time since diagnosis did not appear to moderate the number or severity of residuals Fatigue was the most common residual (93.2%), but pain and motor-related problems were also common. The majority of participants scored within the minimal depression and anxiety ranges on the BDI-II and the STAI-6, suggesting that depression and anxiety were not common long-lasting sequelae to GBS in this sample. Future research using a prospective design could focus on the incidence of depression and anxiety during the actual recovery phase A study that focussed on the perspectives of caregivers and families would also add important information to the small body of literature regarding the psychosocial aspects of GBS.
Keywords: Guillain-Barré syndrome; Psychological aspects